Molecular marker-assisted gene pyramiding in rice for blast resistance, early maturity, salinity and submergence tolerance - Haque, M. A.; Rafii, Mohd Y.; Yusoff, Martini Mohammad; Nusaibah, S. A.; Datta, D. R.; Chowdhary, Mst Farhana Nazneen (Springer Science and Business Media B.V., 2025)
Numerous biotic and abiotic factors have a major influence on rice production; among them, salinity stress, submergence, and rice blast diseases are the main causes of yield losses. The present research was undertaken to pyramid/stack the blast resistance genes Pi2, Pi9, and Piz, the salt resistance gene (QTL Saltol), the submergence resistance gene (QTL Sub1), and the early maturing QTL Hd2, into the single genetic background of Malaysian rice through marker-assisted gene pyramiding. The blast-resistant Putra-1 rice variety was crossed with the salt-tolerant Binadhan-10 rice variety, and the submergence-resistant Putra-2 rice variety was crossed with the early-maturing MR297 rice variety. “True” F1s plants were screened and confirmed the presence of target genes using the tightly linked markers. F2 plants, which are homozygous for all the target genes, or QTLs, were screened and selected using the tightly linked markers, and the selected plants were advanced for future generation with selection based on phenotypic traits. At the F3 generation, a set of 28 promising homozygous lines carrying the Pi2, Pi9, Piz, Sub1, Saltol, and Hd2 genes was identified through gene-specific markers for phenotypic evaluation. The 24 advanced lines were screened for their agronomic performance, resistance against blast diseases, and tolerance to salinity and submergence stress. Among them, GPL-183, GPL-286, GPL-224, GPL-188, GPL-219, GPL-284, GPL-300, GPL-232, and GPL-195 advanced lines were selected for blast resistance, submergence tolerance, and salinity tolerance with early maturity characteristics and also recommended for large-scale field evaluation and future breeding schemes to generate various stress-resistant rice varieties.